In Vitro Comparison of the Internal Ribosomal Entry Site Activity from Rodent Hepacivirus and Pegivirus and Construction of Pseudoparticles. (30th July 2021) - Sims, Stuart; Michaelsen, Kevin; Burkhard, Sara; Fraefel, Cornel
Abstract : The 5′ untranslated region (5′ UTR) of rodent hepacivirus (RHV) and pegivirus (RPgV) contains sequence homology to the HCV type III internal ribosome entry sites (IRES). Utilizing a monocistronic expression vector with an RNA polymerase I promoter to drive transcription, we show cell-specific IRES translation and regions within the IRES required for full functionality. Focusing on RHV, we further pseudotyped lentivirus with RHV and showed cell surface expression of the envelope proteins and transduction of murine hepatocytes and we then constructed full-length RHV and RPgV replicons with reporter genes. Using the replicon system, we show that the RHV NS3-4A protease cleaves a mitochondrial antiviral signaling protein reporter. However, liver-derived cells did not readily support the complete viral life cycle.